The Study of Material Changes in Shot Blasting Process - Kniewald, Dusan; Brezinova, Janette; Guzanova, Anna (Communications - Scientific letters of the University of Zilina, 2004)
The contribution deals with the blasting process from the point of view of degradation phenomena. The interaction of blasting material with the blasted surface causes changes in both blasting material and substrate. In this paper we investigate the wear of various blasting materials and the degradation of the substrate surface. On the basis of the evaluation of studied phenomena in blasting process the classification of upgrading and degrading effects was carried out.